Biocontrol potential and mode of action of the strains EPC 5 and EPC 8 of endophytic bacterium, Bacillus subtilis - G. KARTHIKEYAN; R.SAMIYAPPAN, L. RAJENDRAN*, R. RAMJEGATHESH, V. SHANTHIYAA, T. RAGUCHANDER (Indian Phytopathology, 2012)
The Bacillus subtilis EPC5 and EPC8 are endophytic bacteria, potent biocontrol agents isolated from among ten strains from coconut. Further, the strains EPC5 and EPC8 were characterized in-vitro for possible mechanisms involved in their antagonistic activities against the basal stem rot fungus Ganoderma lucidum on potato dextrose agar plates. An attempt was made for extraction and partial characterization of the extra-cellular diffusible antifungal metabolites by thin layer chromatography that showed many spots throughout the chromatogram after iodine vaporization. The extracellular, methanol soluble, ninhydrinnegative spot showed Rf value of 0.49. Further, Polymerase Chain Reaction analysis showed that the strains EPC5 and EPC8 produces 645bp band representing surfactin antibiotic but no amplification was observed for iturin D antibiotic that is represented by 800bp band in other isolates. The promising isolates can be utilized for the basal stem rot disease management in coconut.